Corporate Social Responsibility: A Recipe for Educational Resource Development in Nigeria Universities - A. J., MEDUPIN; SHITTU, A. A; SOFOLUWE, A. O; ETEJERE, P. A. O; OBA, B. A; OLADEJOBI, J. O (International Journal of Educational Management, 2025)
T here is no doubt that educational resources are important means through which the goals and objectives of university education could be achieved because it is an indispensable ingredient for effective teaching and learning. However, studies have revealed that educational resources in Nigerian tertiary institutions are grossly inadequate. This paper therefore examined the role of Corporate Social Responsibility (CSR) in solving the problem of education resources inadequacy in Nigerian Universities. The focus of the paper will examine concepts of corporate social responsibility and educational resources, principles of corporate social responsibility and corporate social responsibility. This paper also examines concept of corporate social responsibility, concept of educational resources and principle of corporate social responsibility and conclusion was drawn. It was recommended that, it is expedient for beneficiary institutions to ensure sustainable maintenance culture for resources received via corporate social responsibility initiatives.